Gallstone ileus as a cause of mechanical intestinal obstruction: a case report - Acevedo Forero, Ana María (2024)
Biliary ileus is a mechanical intestinal obstruction characterized by symptoms such as abdominal pain, jaundice and fever. The treatment of choice in these cases is associated with a surgical approach according to the clinical condition of the patient. It is important to study this pathology since its timely diagnosis and treatment are essential to avoid serious complications associated with high morbidity and mortality. This article describes a case related to biliary ileus.